Wastewater-based epidemiology of enteric viruses and surveillance of acute gastrointestinal illness outbreaks in a resource-limited region - Chacón Jiménez, Luz María (2021)
Acute gastrointestinal illness (AGI) continues to be an important cause of morbidity and mortality among all ages. This study applied the principles ofwastewater-based epidemiology for the preventive identification of potential outbreaks of acute viral gastroenteritis and hepatitis A by analyzing the presence of human enteric viruses in influents of small municipal wastewater treatment plants (WWTPs) handling domestic sewage, together with public health reports of acute diarrheal and hepatitis A disease in Costa Rica during 2013. Raw wastewater samples were collected during four seasonal periods with different rainfall levels. The presence of five human enteric viruses (rotavirus A, norovirus GI, norovirus GII, enterovirus, and hepatitis A virus) was studied by endpoint and real-time polymerase chain reaction in influents of five WWTPs. Cases of AGI were analyzed using historical public health reports of endemic levels and quartile ranges for each administrative and territorial area where theWWTPs are located and for its surrounding counties. A tendency for a higher rate of positive viral tests was present 1 week before an increase of AGI cases. Epidemiological weeks categorized asOutbreak (above the 75th percentile) and Success (below the 25th percentile) showed statistically significant differences in terms of positive viral test rates (Wilcoxon test, P50.05). Virologicalmonitoring ofwastewater in smallWWTPs is an appropriate model for epidemiological surveillance of diarrheal and hepatitis A diseases in low- and middle-resource countries.